3D Printed Multi‐Cavity Soft Actuator with Integrated Motion and Sensing Functionalities via Bio‐Inspired Interweaving Foldable Endomysium - Zhonggui Fang; Shaowu Tang; Yinyin Su; Xiaohuang Liu; Sicong Liu; Juan Yi; Zheng Wang; Jian S. Dai (Advanced Science)
Abstract The human muscle bundle generates versatile movements with synchronous neurosensory, enabling human to undertake complex tasks, which inspires researches into functional integration of motions and sensing in actuators for robots. Although soft actuators have developed diverse motion capabilities utilizing the inherent compliance, the simultaneous‐sensing approaches typically involve adding sensing components or embedding certain‐signal‐field substrates, resulting in structural complexity and discrepant deformations between the actuation parts with high‐dimensional motions and the sensing parts with heterogeneous stiffnesses. Inspired by the muscle‐bundle multifiber mechanism, a multicavity functional integration (McFI) approach is proposed for soft pneumatic actuators to simultaneously realize multidimensional motions and sensing by separating and coordinating active and passive cavities. A bio‐inspired interweaving foldable endomysium (BIFE) is introduced to construct and reinforce the multicavity chamber with optimized purposive foldability, enabling 3D printing single‐material fabrication. Performing elongation, contraction, and bidirectional bending, the McFI actuator senses its spatial position, orientation, and axial force, based on the kinematic and sensing models built on multi‐cavity pressures. Two McFI‐actuator‐driven robots are built: a soft crawling robot with path reconstruction and a narrow‐maneuverable soft gripper with object exteroception, validating the practicality in stand‐alone use of the actuator and the potential for intelligent soft robotic innovation of the McFI approach.